Right ventricular systolic function in Nigerians with heart failure secondary to hypertensive heart disease - Ifeoluwa, Adewoye A (Afr Health Sci, 2019)
BACKGROUND: Right ventricular (RV) dysfunction has been shown to be a major contributor to the adverse outcomes in subjects with heart failure. Few studies evaluating the right ventricle in heart failure subjectshave been carried out in Sub-Saharan Africa. This studywas therefore designed to evaluate the right ventricular systolic function in subjects with heart failure secondary to hypertensive heart disease presenting to the University College Hospital, Ibadan Nigeria. METHODOLOGY: Seventy-six subjects with heart failure secondary to hypertension and 92 normal controls underwent clinical, electrocardiographic and echocardiographic evaluation. Indices of right ventricular systolic function that were measured include tricuspid annular plane systolic excursion (TAPSE), tissue Doppler derived tricuspid peak systolic lateral annulus velocity(S′) and right ventricular fractional areachange(RVFAC). RESULTS: Sixty-two (81.6%) heart failure subjects had right ventricular systolic dysfunction, 31(40.8%) had abnormal TAPSE, 42(55.5%) had abnormal S′ while 49(64.5%) had abnormal RVFAC. Elevated pulmonary artery systolic pressure was found in 25(32.9%) of the subjects. There was no relationship between the indices of right ventricular systolic function and the estimated systolic pulmonary artery pressures. The independent predictor of right ventricular systolic dysfunction was the right atrial size. CONCLUSION: Right ventricular systolic function is impaired in patients with heart failure secondary to hypertensive heart disease. There is no relationship between the indices of right ventricular systolic function and systolic pulmonary artery pressure. Further studies are needed to assess right ventricular systolic function in Nigerians.